2003
DOI: 10.1002/ar.b.10003
|View full text |Cite
|
Sign up to set email alerts
|

Integration of advanced technologies to enhance problem‐based learning over distance: Project TOUCH

Abstract: Distance education delivery has increased dramatically in recent years as a result of the rapid advancement of communication technology. The National Computational Science Alliance's Access Grid represents a significant advancement in communication technology with potential for distance medical education. The purpose of this study is to provide an overview of the TOUCH project (Telehealth Outreach for Unified Community Health; http://hsc.unm.edu/touch) with special emphasis on the process of problem-based lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…8 Others are under development, including training programs using simulation and, distributed virtual reality. [9][10][11][12][13][14][15][16] Current efforts are aimed at exploring the integration of other HIT efforts with telehealth in coordination with LCF Research (http:// www.lcfresearch.org/) and their statewide HIE called the New Mexico Health Information Collaborative, as well as the Health Information Regional Extension Center, fostering adoption of electronic health records among primary care providers and helping them to achieve meaningful use.…”
Section: Description Of Context Setting and Role Of Telemedicine Wimentioning
confidence: 99%
“…8 Others are under development, including training programs using simulation and, distributed virtual reality. [9][10][11][12][13][14][15][16] Current efforts are aimed at exploring the integration of other HIT efforts with telehealth in coordination with LCF Research (http:// www.lcfresearch.org/) and their statewide HIE called the New Mexico Health Information Collaborative, as well as the Health Information Regional Extension Center, fostering adoption of electronic health records among primary care providers and helping them to achieve meaningful use.…”
Section: Description Of Context Setting and Role Of Telemedicine Wimentioning
confidence: 99%
“…[7][8][9][10][11][12][13] These modalities have also been applied to PBL. [14][15][16][17][18] Results of the use of patient simulators and MMCCSS in PBL indicate that students perceived an increase in their clinical competence due to the hands-on nature of practicing patient care via case simulation 14,19 and indicated that the simulations were a superior Feature Editor's Note: This article describes a study that evaluated the effect of using DxR, a multimedia clinical case simulation software application developed in the 1990s. Using two student cohorts, the study compared clinical training and outcomes using enhanced problem-based learning with DxR and found significant advantages with increased use of multimedia software.…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant research on using interactive multimedia for learning and training. The authors in [14] discuss the delivery of Tele-health related material for teaching medical curriculum. An example of how to deal with traumatic head injuries is demonstrated as an example of the system.…”
Section: Introductionmentioning
confidence: 99%